Exploring the Implementation of Unplugged Coding Media in Early Childhood Education - Rosyida Ani Dwi Kumala; Lusila Andriani Purwastuti (Universitas Sebelas Maret, 2026)
The Rapid technological advancement has encouraged the introduction of computational thinking skills from early childhood. One relevant approach is unplugged coding activities, which introduce basic programming concepts without using digital devices. This study aims to explore the use of unplugged coding media in early childhood education and how the media facilitate children’s learning experiences. The study employed a qualitative approach with an exploratory case study design. The participants consisted of five children aged 5–6 years and one teacher from an early childhood education institution in Surakarta. Data were collected through observation, interviews, and documentation, while data analysis employed the interactive model of Miles, Huberman, and Saldana. The findings revealed that unplugged coding media created active and exploratory learning experiences through activities such as arranging instructions, following sequences, and solving simple problems. Media such as path boards, direction cards, and code symbols helped children understand algorithmic concepts concretely. In addition, these activities supported the development of logical thinking, collaboration, and problem-solving skills. The teacher’s role as a facilitator was identified as a key factor in the successful implementation of unplugged coding activities. Therefore, unplugged coding media have strong potential as an innovative learning medium that aligns with the developmental characteristics of early childhood learners.